PENGEMBANGAN LEMBAR KERJA SISWA PADA PEMBELAJARAN IPA BERBASIS INKUIRI TERBIMBING UNTUK KELAS V SEKOLAH DASAR - Eni Marta (JURNAL PENDIDIKAN ROKANIA, 2017)
The purpose of this study was to develop and produce the student worksheet on Guided Inquiry by several criteria such as valid, practical, and effective. This research was conducted in SDN 002 and in SDN 003 Rambah. The development model used is the model 4-D comprising the step of defining, designing, development and deployment. The results of the study at the planning stage is obtained syllabus, lesson plan, and student worksheet that is designed to follow the steps Guided Inquiry learning model. The results of the study at this stage of development the validity test data showed that the average percentage of Syllabus is lesson plan is 87.5%, the average percentage of implementation lesson plans is 83%, the percentage of student worksheets of validation of the instrument was 86.2%, the percentage of student worksheets of validation media is 90%, the percentage of student worksheets of validation material was 83% and the percentage is 90% validation language. Implementation of test result practicalities of lesson plan percentage is 88.9%, the questionnaire responses of teachers is 87% and student questionnaire responses was 92.6%. Furthermore, the effectiveness of the test results obtained from the student activity by 85.9% and the percentage of aspects of the knowledge obtained by percentage of 89%, the assessment of students attitudes to the average percentage of 88.1%. This research resulted in the Guided Inquiry-based science learning with the criteria of very valid, very practical and effective